EFFECT OF MICROPLASTIC INTAKE ON INTESTINAL AND PANCREATIC CELL DAMAGE - Steven Wijono; Irene Lingkan Parengkuan; Shella Morina; Vincentius Diamantino Supit; David Karunia Jaya; Leonardo Suryanto Wicaksono; Michael Christian Iskandar (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Introduction: Microplastics are plastic particles that result from the breakdown of larger plastic particles into smaller pieces and are found in natural environments such as oceans, beaches, and land. Microplastics harm the environment and affect human health. The main entrance of microplastics into the body is the digestive system, through the food and drinks we consume daily. Various investigations have shown that human feces samples contain microplastics that come from ingestion of contaminated food. If it continues, it can damage our body cells. Objective: This research aims to demonstrate that oral administration of microplastics can impair the function of the small intestine, large intestine, and pancreas in rattus of the strain Rattus norvegicus wistar. Method: This study is a quantitative analytic investigation employing an experimental methodology on experimental animals. In this work, the experimental animals were separated into six groups, including the control group and the treatment groups X1, X2, X3, X4, and X5; microscopic observations were conducted 90 days after the microplastics were administered. Results: The comparison of the control group with each exposure group to the small intestine revealed significant results in the Pearson correlation test in groups K with X2, X3, and X4 and the Mann-Whitney difference test in groups K with X2 and X4. Comparing the control group with each exposure group to the large intestine revealed no significant results in the Pearson correlation test and the Mann-Whitney difference test. Conclusion: The correlation test results between the control group and the complete exposure groups revealed significant outcomes in the small intestinal tissue but not in the large intestine and pancreas tissue.